Populations: Mouse, Monkey, and Man - King, John A. (Contemporary psychology, 1981)
Reviews the book, Biosocial Mechanisms of Population Regulation edited by Mark Nathan Cohen, Roy S. Malpass, and Harold G. Klein (1980). The book extends the principle that each population is unique by making the distinction between mankind and other animals. Information about regulatory mechanisms in nonhuman populations cannot be transferred directly to human populations. The volume publishes a symposium held in the spring of 1978 on the Plattsburgh Campus at SUNY and hosted by the editors, who represent the three disciplines. Their enthusiasm for the subject material is revealed by the frequency of their distracting footnotes, which usually serve to draw attention to similar or contrasting statements among the participants. Neither scientist nor statesman will learn what regulates populations from this book. There are no easy answers. Additional conferences are needed to continue the flow of information among various disciplines. (PsycINFO Database Record (c) 2016 APA, all rights reserved)